The Effect of Problem-Based Learning Model With Audio Visual Media on the Learning Outcomes of The Students on Environmental Pollution Material - Sabrina Trie Hapsari; Suratno Suratno; Kamalia Fikri (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
Education plays a very important role and factor in human life as it becomes a vehicle to create qualified human resources in terms of knowledge and skill. In implementing this educational objective, a learning model is required to be able to motivate the students in learning so that the students’ cognitive and effective increase. Problem-based learning model with audio visual media is considered to be one of the learning models which can improve the students. This study aimed to determine the effect of the problem-based learning model with audiovisual media on cognitive learning outcomes of the seventh-grade students at SMP Negeri 9 Jember on environmental pollution subject. Quasi-experimental research with control class and the experimental class was applied in this research. In the experimental class, learning activity was carried out by applying problem-based learning model with audiovisual media whereas the Discovery Learning model with an image as its media was taught in the control class. The data of the students' cognitive learning outcomes were obtained through the pre-test and post-test scores, the students' affective learning outcomes were collected through direct observation in a classroom by using observation sheet consisting of five aspects in which they were activeness, responsibility, collaboration, discipline, and interaction. The application of problem-based learning model with audiovisual media had a significant effect with a probability as much as 0,000. The affective learning outcomes influenced significantly with the probability value of the T-test was 0,000